Influence of Preventive Mechanisms on Counter Terrorism Measures in Garissa University in Kenya - Ringera, Esther Kinanu; Kaguta, Joyce; Sang, Anne (Advances in Social Sciences Research Journal, 2022)
This paper was derived from a study that was carried out in Garissa University in Kenya. Counter Terrorism Measures are the world’s most effective actions of dealing with the threatening effects and consequences of terrorism. Having appropriate preventive mechanisms is a contribution by the government and security planners to ensure the nation and the universities are secure for learning to progress without any disruptions. The specific objectives of this study were to evaluate the influence of preparedness, assess the influence of preventive mechanisms, analyze the influence of challenges and establish the influence of the role of stakeholders in Counter Terrorism Measures in Garissa University in Kenya. Rational choice theory and descriptive research design was employed, targeted 105 students and staff. Data was collected using a semi structured questionnaire, analyzed using (SPSS) version 22.Results revealed that preparedness, preventive mechanism, challenges, and role of stakeholders had a statistically positive influence on CT measures in Garissa University in Kenya. These accounted to 49.7% of the variations in counter terrorism measures in Garissa University, this indicates that other factors not studied contributes to the other 50.3%.The study recommends more resources for counter terrorism measures, improvement on intelligence sharing, provision of modern communication systems and the University to collaborate more with other agencies to ensure laws are developed to help in monitoring of internet The study has contributed to theory building; informs the policy makers , on the importance continuous improvement Counter Terrorism Measures.